Systematic Assessment of Hebius beddomei (Günther, 1864) (Serpentes: Colubridae: Natricinae) with Description of a New Genus and a New Allied Species from the Western Ghats, India - Harshil Patel; Tejas Thackeray; Patrick D. Campbell; Zeeshan A. Mirza (Taxonomy, 2023)
Hebius beddomei (Günther, 1864) is an endemic natricine colubrid snake species from the biodiverse Western Ghats, India. A recent molecular phylogeny provided evidence for the paraphyly of the genus Hebius, with Hebius beddomei recovered as sister to a clade containing Fowlea and Atretium. Freshly collected specimens and existing museum material allowed us to elucidate the generic status of the species and identify two distinct populations, one of which is described as a new species. A new genus, Sahyadriophis gen. nov., is proposed to accommodate Sahyadriophis beddomei gen. et. comb. nov., and Sahyadriophis uttaraghati gen. et. sp. nov. is described as a new species from the northern part of the range. The discovery of a new Oligocene divergent lineage, Sahyadriophis gen. nov., highlights the role of the Western Ghats as a source of relic lineages.